A semelparous fish continues upstream migration when exposed to alarm cue, but adjusts movement speed and timing. (November 2016) - Luhring, Thomas M.; Meckley, Trevor D.; Johnson, Nicholas S.; Siefkes, Michael J.; Hume, John B.; Wagner, C. Michael
Abstract : Animals make trade-offs between predation risk and pursuit of opportunities such as foraging and reproduction. Trade-offs between antipredator behaviours and foraging are well suited to manipulation in laboratory and field settings and have generated a vast compendium of knowledge. However, much less is known about how animals manage trade-offs between predation risk and pursuit of reproductive opportunities in the absence of the confounding effects of foraging. In the present study, we investigated how the nonfeeding migratory life stage of sea lamprey, Petromyzon marinus, responds to odour from dead conspecifics (a cue that induces avoidance behaviours in laboratory and field studies). We released groups of PIT-tagged sea lamprey 65 m from the shore of Lake Michigan or 287 m upstream in Carp Lake River and used antennas to detect their movements in the river. As the breeding season progressed, sea lamprey initiated upstream movement earlier and were more likely to enter the river. Sea lamprey that began the night in Lake Michigan entered Carp Lake River at higher rates and accelerated upstream when exposed to high concentrations of alarm cue, consistent with animals attempting to minimize time spent in risky areas. Sea lampreys that began the night in the river delayed upstream movement when exposed to alarm cue, consistent with animals sheltering and gathering information about a source of risk. We attribute this context-specific reaction to alarm cue to differences in perceived vulnerability to predation in sheltered positions in the river versus exposed positions in the lake. Once in the river, the vast majority of sea lamprey moved upstream independent of alarm cue or Julian date. Although life-history-induced time and energy budgets place rigid constraints on the direction of migration, sea lamprey attend to predation risk by modifying movement timing and speed. Highlights: We applied alarm cue across a river during an upstream migration of sea lamprey. Alarm cue alters sea lamprey movement speed and timing but not migratory direction. Timing of upstream movement was context specific, differing by release location. Nonfeeding sea lamprey appear to balance risk and reproductive opportunities.